Process Simulation Analysis of HF Stripping - Thaer A. Abdulla (Tikrit Journal of Engineering Sciences, 2015)
HYSYS process simulator is used for the analysis of existing HF stripping column in LAB plant (Arab Detergent Company, Baiji-Iraq). Simulated column performance and profiles curves are constructed. The variables considered are the thermodynamic model option, bottom temperature, feed temperature, and column profiles for the temperature, vapor flow rate, liquid flow rate and composition. The five thermodynamic models options used (Margules, UNIQUAC, van laar, Antoine, and Zudkevitch-Joffee), affecting the results within (0.1-58%) variation for the most cases.         The simulated results show that about 4% of paraffin (C10 & C11) presents at the top stream, which may cause a problem in the LAB production plant. The major variations were noticed for the total top vapor flow rate with bottom temperature and with feed composition. The column profiles maintain fairly constants from tray 5 to tray 18. The study gives evidence about a successful simulation with HYSYS because the results correspond with the real plant operation data.